2014
DOI: 10.1177/1084822314530991
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Testing of the Home Care Education, Assessment, Remote-Monitoring, and Therapeutic Activities Intervention

Abstract: The primary aim of this pilot study was to develop, implement, and test the feasibility and efficacy of the Home Care Education, Assessment, Remote-Monitoring, and Therapeutic Activities (HEART) trial, a nurse-directed multicomponent home care intervention. A total of 50 patients with a primary diagnosis of heart failure (HF) were assigned to the intervention ( n = 26) or control group ( n = 24) according to geographical location in a large multibranch Medicare-certified home health agency. Forty-six patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…86 Other outcome measures included changes in anthropometrics, cardiovascular and diabetes risk reduction, and behavior change. Anthropometric outcomes included changes in body weight, 17,22,31,32,67,73,85,[88][89][90]93,95,99,100,112 decreases in waist circumference, 19,32,75,76,95,100 and reductions in body mass index. 19,26,32,103,112 Results related to cardiovascular risk factors included changes in blood lipid levels 75,100 and improved blood pressure.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…86 Other outcome measures included changes in anthropometrics, cardiovascular and diabetes risk reduction, and behavior change. Anthropometric outcomes included changes in body weight, 17,22,31,32,67,73,85,[88][89][90]93,95,99,100,112 decreases in waist circumference, 19,32,75,76,95,100 and reductions in body mass index. 19,26,32,103,112 Results related to cardiovascular risk factors included changes in blood lipid levels 75,100 and improved blood pressure.…”
Section: Study Characteristics and Resultsmentioning
confidence: 99%
“…Sixteen studies (21%) were characterized as feasibility trials by the study authors as a sub-set of the major design types reported. 26,28-30,33,38-40,63,65,90-95 Only 28 of the studies (36%) were registered through the U.S. National Library of Medicine on clinicaltrials.gov. 18-20,23-25,30,31,40,64,67,70,71,73,74,78,79,81-84,86,88,89,95-98 The clinical settings where these interventions took place revealed that the majority were in primary care or family medicine clinics (42%) 18-20,22,24,25,28,30,32,35,36,39,63,67,72,73,77,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation